2019
DOI: 10.1080/13102818.2019.1649987
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management and anaesthetic considerations for adult patients with Gilbert’s syndrome and oral cancer: review and case report

Abstract: Gilbert's syndrome is the most common cause of hereditary hyperbilirubinemia and poses a clinical challenge for anaesthesiologists. The decreased activity of bilirubin uridine glucuronyl transferase can lead to toxicity for usual doses of most anaesthetic agents. We review and discuss the approach to successful and safe anaesthesia management in these patients and we report a case of a 48-year-old male patient with Gilbert's syndrome submitted to maxillofacial surgery under general anaesthesia. The recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The clinical manifestations only become more noticeable in certain situations such as fatigue, exercise, febrile illness, fasting, and alcohol ingestion especially in older patients. 6 In our case report, it was found that the patient showed a yellow tinge as oral manifestation in the lower lip, hard palate, the floor of the mouth, gingiva, and tongue. No abnormalities were noted regarding teeth such as number, shape, or size.…”
Section: Discussionmentioning
confidence: 66%
“…The clinical manifestations only become more noticeable in certain situations such as fatigue, exercise, febrile illness, fasting, and alcohol ingestion especially in older patients. 6 In our case report, it was found that the patient showed a yellow tinge as oral manifestation in the lower lip, hard palate, the floor of the mouth, gingiva, and tongue. No abnormalities were noted regarding teeth such as number, shape, or size.…”
Section: Discussionmentioning
confidence: 66%
“…As this is the first case report to document this concurrence, more such cases need to be documented before we can ascertain any association. Gilbert's syndrome is usually asymptomatic and is aggravated following a triggering factor such as stressful events such as surgery, rigorous exercise or sports activities, fasting, and alcohol intake [10]. There are reports of many cases of Gilbert's syndrome which has been reported during pregnancy [9] and as a postsurgical complication [18].…”
Section: Discussionmentioning
confidence: 99%
“…Gilbert's syndrome is a genetic disorder which is caused due to the deficiency of the enzyme uridine diphosphoglucuronateglucuronosyltransferase 1A1 (UGT1A1) which is involved in the process of conjugation of bilirubin, thereby resulting in unconjugated hyperbilirubinemia [9]. Gilbert's syndrome is generally asymptomatic and is aggravated in association with certain triggering factors [10]. Oral manifestations of Gilbert's syndrome have not been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Signs and symptoms of GS are jaundice, nausea, malaise, right hypochondrium discomfort, and abdominal pain. [ 2 ]…”
mentioning
confidence: 99%
“…Isoflurane preserves hepatic blood flow. [ 2 ] Acetaminophen is not metabolized by glucuronyl transferase but is metabolized by another enzyme which too may be deficient in GS, making these patients susceptible to toxicity. Surgical stress, anesthesia, fasting, infection, exercise, excess alcohol consumption, fatigue, and menstruation exacerbate the symptoms of GS.…”
mentioning
confidence: 99%